1984
DOI: 10.1007/bf02541646
|View full text |Cite
|
Sign up to set email alerts
|

Diesel engine evaluation of a nonionic sunflower oil‐aqueous ethanol microemulsion

Abstract: A nonionic sunflower oil-aqueous ethanol microemulsion was formulated, characterized and evaluated as a fuel in a direct injection, turbocbarged, intercooled, 4-cylinder Allis-Chalmers diesel engine during a 200 hr EMA cycle laboratory screening endurance test. Differences in engine operation between a baseline Phillips 2D reference fuel and the experimental fuel were observed. The major problem experienced while operating with the microemulsion was an incomplete combustion process at low-load engine operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(28 citation statements)
references
References 6 publications
0
28
0
Order By: Relevance
“…Moreover, the deposits formed in the exhaust valve using both fuels were brittle and could be easily detached from the valve surface. In a study, Ziejewski et al (1984) formulated, characterized, and evaluated a nonionic sunflower oil-aqueous ethanol microemulsion as fuel in a diesel engine during a 200 h endurance test. After each durability test, the carbon, sludge and varnish deposits were rated to directly measure the wear of the engine components.…”
Section: Deposit Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the deposits formed in the exhaust valve using both fuels were brittle and could be easily detached from the valve surface. In a study, Ziejewski et al (1984) formulated, characterized, and evaluated a nonionic sunflower oil-aqueous ethanol microemulsion as fuel in a diesel engine during a 200 h endurance test. After each durability test, the carbon, sludge and varnish deposits were rated to directly measure the wear of the engine components.…”
Section: Deposit Growthmentioning
confidence: 99%
“…None of the methods were capable of measuring the mass of deposits stuck in the piston ring accurately. Simillar studies were conducted by Ziejewski et al (1983 and1984) in which all pistons showed significantly greater carbon and lacquer buildups in the ring grooves and on the piston lands, as well as on the piston undercrowns and skirts. Moreover, in a comparative study, Agarwal et al (2011) in a qualitative analysis of soot formation on engine components under EGR operation condition found that higher soot deposits were formed on the cylinder head, injector tip, and piston crown when EGR was used compared with the condition where the engine was operated without EGR.…”
Section: Deposit Growthmentioning
confidence: 99%
“…The durabilities were not determined. Ziejewski et al (1984) prepared an emulsion of 53% (vol) alkali-re®ned and winterized sun¯ower oil, 13.3% (vol) 190-proof ethanol and 33.4% (vol) 1-butanol. This nonionic emulsion had a viscosity of 6.31 cSt at 40°C, a cetane number of 25 and an ash content of less than 0.01%.…”
Section: Microemulsionsmentioning
confidence: 99%
“…In addition, biodiesel contains virtually no sulfur or aromatics, and the use of biodiesel in a conventional diesel engine results in substantial reduction of unburned hydrocarbons, carbon monoxide, particulate matter and the other emissions compared to petro-diesel on its combustion in the diesel engine [4]. Microemulsions [5][6][7], transesterification and thermal cracking (pyrolysis) [8,9] are different techniques used in biodiesel production.…”
Section: Introductionmentioning
confidence: 99%